Evaluation of color perception in individuals addicted to narcotic substances in the Farnsworth-Munsell 100-Hue test - Krystyna Nadolska; Roman Goś (Nofer Institute of Occupational Medicine, 2016)
Background: The aim of the study was to assess color perception in the Farnsworth-Munsell 100-Hue test in individuals addicted to narcotic substances, and to analyze the acquired color vision disorders, depending on the duration of addiction and abstinence. Material and Methods: Ninety-five persons were qualified for the study. All the subjects were divided into 3 groups. Group I (drug addicts) comprised 45 individuals addicted to narcotic substances and nicotine. Group II (smokers) consisted of 30 individuals addicted only to nicotine, and group III (abstinents) included 20 individuals free of addictions. In all the study groups anamnesis, survey, standard ophthalmological examination and the Farnsworth-Munsell 100-Hue test were performed. Results: In the Farnsworth-Munsell 100-Hue test the mean values of total error score (TES) for the purposes of the analysis, expressed in the values of square root (√TES), proved to be significantly higher in group I than in the two other groups (p < 0.001). In group I, the √TES values exceeding critical values of age norms occurred significantly more frequently than in groups II (p < 0.01) and III (p < 0.05). A positive correlation between duration of addiction and the √TES values was indicated (ρ = 0.234, p < 0.05). The longer was the period of abstinence, the lower were the √TES values, indicating the improved ability to distinguish between colors. Conclusions: The Farnsworth-Munsell 100-Hue test proved useful in the detection and assessment of acquired dyschromatopsy induced by narcotic substances. The observed disorders appeared to be dependent on the duration of addiction and abstinence. Med Pr 2016;67(6):777-785